2021
DOI: 10.36660/ijcs.20210076
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Cardiovascular Disease Risk Factors in Adults in São Paulo, Brazil: Prevalence and Associated Factors in 2008 and 2015

Abstract: Cardiovascular diseases (CVDs) are the main cause of morbidity and mortality worldwide, including in Brazil, where approximately 395,700 deaths (30% of total deaths) registered in 2018 were due to CVDs. 1 Considering the negative impact on individual's health, health systems, and the economy, monitoring CVD risk factors become imperative for both CVD prevention and control. 2 Moreover, many risk factors for CVDs are also risk factors for other non-communicable diseases (e.g., cancer), and are associated with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Conversely, older adults had the highest scores, but improvements are still needed to prevent complications resulting from high BP. From 2008 to 2015, São Paulo experienced a rise in the prevalence of intermediate factors of CVDs, where HTN exhibited the second-largest increase among the factors evaluated, with a 1.3-fold rise, surpassed only by diabetes [ 66 ]. This surge in healthcare demands presents a substantial challenge, calling for strategic planning in both health and economic public policies.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, older adults had the highest scores, but improvements are still needed to prevent complications resulting from high BP. From 2008 to 2015, São Paulo experienced a rise in the prevalence of intermediate factors of CVDs, where HTN exhibited the second-largest increase among the factors evaluated, with a 1.3-fold rise, surpassed only by diabetes [ 66 ]. This surge in healthcare demands presents a substantial challenge, calling for strategic planning in both health and economic public policies.…”
Section: Discussionmentioning
confidence: 99%
“…•Por fim, dados de duas coortes do estudo transversal Health Survey of São Paulo focusing on Nutrition ( ISA-Nutrition ), uma sub-amostra do Health Survey of São Paulo ( ISA-Capital ), conduzido em 2008 e 2015, mostraram associação de excesso de peso corporal com maior chance de apresentar todos os outros fatores de risco analisados. 381 A distribuição da gordura corporal é também um determinante de risco, sendo menor acúmulo de gordura corporal considerado protetor em oposição a obesidade abdominal. Oliveira et al .…”
Section: Impacto Na Saúde Cardiovascularunclassified
“…•Finally, data from two cohorts of the cross-sectional Health Survey of São Paulo focusing on Nutrition (ISA-Nutrition study ), a sub-sample of the Health Survey of São Paulo (ISA-Capital ), carried out in 2008 and 2015, showed that excess body weight was associated with higher odds of presenting all the other risk factors analyzed. 381 The distribution of body fat is also a determinant of risk, with lower body fat accumulation being considered protective as opposed to abdominal obesity. Oliveira et al .…”
Section: Impact On Cardiovascular Healthmentioning
confidence: 99%